Alterations in phosphorylated cAMP response element‐binding protein (pCREB) signaling: an endophenotype of lithium‐responsive bipolar disorder?. (14th November 2013) - Alda, Martin; Shao, Li; Wang, Jun‐Feng; de, Catalina Lopez; Jaitovich‐Groisman, Iris; Lebel, Veronique; Sun, Xiujun; Duffy, Anne; Grof, Paul; Rouleau, Guy A; Turecki, Gustavo; Young, L Trevor
<x xml:space="preserve">Abstract</x> Objectives Abnormalities of signal transduction are considered among the susceptibility factors for bipolar disorder (BD). These include changes in G‐protein‐mediated signaling and subsequent modification of gene expression via transcription factors such as cAMP response element‐binding protein (CREB). Methods We investigated levels of CREB in lymphoblasts from patients with BD, all responders to lithium prophylaxis (n = 13), and healthy control subjects (n = 15). Phosphorylated CREB (pCREB) was measured by immunoblotting in subjects with BD (n = 15) as well as in their affected (n = 17) and unaffected (n = 18) relatives, and healthy controls (n = 16). Results Basal CREB levels were comparable in patients and control subjects and were not changed by lithium treatment. pCREB levels were increased in both patients and their relatives compared to controls (p = 0.003). Forskolin stimulation led to a 24% increase in pCREB levels in cells from healthy subjects (p = 0.002) but not in the other three groups. When using basal and stimulated pCREB levels as a biochemical phenotype in a preliminary linkage study, we found the strongest support for linkage in regions largely overlapping with those showing linkage with the clinical phenotype (3p, 6p, 16p, 17q, 19q, and 21q). Conclusions Abnormal pCREB signaling could be considered a biochemical phenotype for lithium‐responsive BD.